Initial Results of the Master's Degree Programme in "Leadership in Medicine" – Impact on hospital-based follow-on training of doctors - Wulfert, Chris-Henrik; Hoitz, Joachim; Senger, Ulrike (GMS Journal for Medical Education, 2017)
Objective: This pilot project, which was jointly conducted by a hospital and a university, describes the development of the Master's Degree Programme in Leadership in Medicine, a course designed to supplement medical specialty training. The aim of the pilot project is to demonstrate how hospital-based projects on personnel and organisational development undertaken under academic supervision can be used to increase leadership responsibility among doctors whose duties include providing initial and follow-on training and to professionalise medical specialty training as a leadership task. This need arose from the nationwide requirements and an internal audit regarding follow-on training. The version of the degree programme described below aims to further the personnel development of the participants in the field of didactics. Method: Each of the nine modules is made up of two classroom-based phases and one distance learning phase. The distance learning phase involves undertaking hospital-based projects on personnel and organisational development under academic supervision. The pilot phase participants were hospital doctors who, as part of their duties, hold leadership responsibility or are involved in the follow-on training of doctors.Results: The 17 participants successfully implemented more than 30 hospital-based projects during the distance learning phases of the nine modules. These projects included the development of medical specialty curricula, relevant didactic methods and evaluation design and were subsequently presented and subjected to reflection in interdisciplinary groups. The project presentation together with the project report were regarded as proof of competency. Conclusion: In addition to enhancing participant competency, the degree model described, which interlinks theory and practice, promotes organisational development through the implementation of projects undertaken under academic supervision. This has a double impact on the quality of medical follow-on training at the hospital where the participant is based, for not only is the individual's didactic competency enhanced, but so is the "learning organisation" as a whole as a result of continuous project orientation.